Peningkatan Aktivitas Belajar Siswa Melalui Model Pembelajaran Talking Stick pada Mata Pelajaran IPS di SMP Negeri 02 Ranah Pesisir - Syamsiwarni Syamsiwarni (Journal of Education on Social Science (JESS), 2018)
This study tried to proof if the use of Talking Stick learning model could improve student activities in Social Science subject matter in SMPN 2 Ranah Pesisir. This study was a classroom action research conducted at grade VIII 2 SMPN 2 Ranah Pesisir in the first semester of Academic Year of 2012/2013 with a population consisted of 34 students. This study was conducted in two cycles. Each cycle was carried out with three meetings. From the results of the study it could be concluded that there was a significant increase in students' activities using Talking Stick learning model. By applying this model, students’ activities increased. In addition, they were more motivated to learn because they thought this model was interesting and fun. The results of this study showed the increasing of Social Science learning activities after the implementation of cooperative learning with Talking Stick model. It means that the Talking Stick model could improve student learning activities in Social Science subject at grade VIII 2 SMPN 2 Ranah Pesisir.